Does training with PowerCranks(tm) affect economy of motion, cycling efficiency, oxygen uptake and muscle activation patterns in trained cyclists? - Burns, J. (Edith Cowan University, 2008)
PowerCranks(tm) are claimed to increase economy of motion and cycling efficiency by reducing the muscular recruitment patterns that contribute to the resistive forces occurring during the recovery phase of the pedal stroke. However, scientific research examining the efficacy of training with PowerCranks(tm) is lacking. Therefore, the purpose of this study was to determine if five weeks of training with PowerCranks(tm) improves economy of motion (EOM), gross efficiency (GE), oxygen uptake (V.O2) and muscle activation patterns in trained cyclists. Sixteen trained cyclists were matched and paired into either a PowerCranks(tm) (PC) or Normal Cranks (NC) training group. Prior to training, all subjects completed a graded exercise test (GXT) using normal bicycle cranks. Additionally, on a separate day the PC group performed a modified GXT using PowerCranks? and cycled only until the end of the 200W stage (PCT). During the GXT and PCT, FeO2, FeCO2 and V.E were measured to determine EOM, GE and V.O2max. Integrated electromyography (iEMG) was also used to examine selected muscular activation patterns. Subjects then repeated the tests following the completion of training on their assigned cranks.